DETERMINAN PRICE EARING RATIO PADA EMERGING MARKET: STUDI EMPIRIS PADA INDEKS KOMPAS 100 - Tenaya, Luh Gede Audhya Candranithi; Diantini, Ni Nyoman Ayu (E-Jurnal Manajemen, 2016)
Price Earning Ratio is a ratio for valuing a company that measures its current share price relative to its earnings per-share. This study aimed to examine whether the factors that influence the price earning ratio in developed countries could also affect the price earning ratio in developing countries, especially in Indonesia and the dividend payout ratio, return on assets, earnings growth and earnings variability as a factor affecting the price earning ratio the Indeks Kompas100 during 2011-2014. The sample in this study is a company incorporated in the Indeks Kompas 100 during the period of 2011-2014. The method used is multiple linear regression. This study proves that the return on assets , earnings growth and earnings variability is partially significant effect on the price earning ratio affects the Compass 100 Index , while the dividend payout ratio does not significantly influence the price earnings ratio on the Indeks Kompas 100. The implications of this research are investors in assessing stocks in emerging markets can use return on assets , earnings growth and earnings variability as factors to be considered in assessing the stock.
Keywords: price earning ratio, dividend payout ratio, return on asset, earning growth, earning variability, emerging market.